Efforts to Improve the Knowledge and Skills of Health Cadres in the Prevention and Early Detection of Non-Communicable Diseases - Hajrah, Waode; Sari, Gita Nirmala; Syarifah, Syarifah (Jurnal Pengabdian Masyarakat Borneo, 2024)
Non-communicable diseases (NCDs), such as diabetes mellitus (DM) and hypertension, represent an increasing global health burden. In Indonesia, the prevalence of DM reaches 10.9%, while hypertension reaches 34.1%. This community engagement activity aims to enhance the knowledge and skills of Integrated Healthcare Center (IHC) cadres in early detection of NCDs, such as hypertension, and to increase community participation in prevention efforts. The community engagement activity was carried out through coordination among the outreach team, neighborhood leaders (RW), and community unit leaders (RT). The activity included the development of educational materials and training sessions for IHC cadres on blood pressure measurement skills. Evaluation showed that 85% of the 30 IHC cadre participants were able to correctly answer questions after the training. The cadres also demonstrated increased motivation and active participation in blood pressure measurement. The community engagement activity successfully achieved its goal of improving the knowledge and skills of IHC cadres in early detection of NCDs while fostering active participation in preventing non-communicable diseases. The evaluation confirmed the positive impact of this program in raising public awareness of health issues.